Genital lichen sclerosus and melanoma; a systematic review. Issue 2 (11th December 2022) - Sim, Sharmaine J. Y.; Dear, Katherine; Mastoraki, Evanthia; James, Mariel; Haider, Aiman; Ellery, Peter; Freeman, Alex; Alnajjar, Hussain M.; Muneer, Asif; Watchorn, Richard; Kravvas, Georgios; Bunker, Christopher B.
Abstract: Background: Lichen sclerosus (LSc) is a chronic, inflammatory, destructive skin disease with a predilection for the genitalia (GLSc). An association with vulval (Vu) and penile (Pe) squamous carcinoma (SCC) is now well established but melanoma (MM) has only rarely been reported complicating GLSc. Methods: We have performed a systematic literature review of GLSc in patients with genital melanoma (GMM). Only articles that mentioned both GMM and LSc affecting either the penis or vulva were included. Results: Twelve studies with a total of 20 patients were included. Our review shows that an association of GLSc with GMM has been more frequently reported in women and female children than men viz, 17 cases compared with three. It is notable that five of the cases (27.8%) concerned female children aged under twelve. Discussion: These data suggest a rare association between GLSc and GMM. If proven, there arise intriguing questions about pathogenesis and consequences for counselling of patients and follow‐up. Abstract : A systematic literature review on the association between genital lichen sclerosus (GLSc) and genital melanoma (GMM).